Coplanar Tetracyclic π‐Excess σ2P Ligands. Issue 24 (13th June 2013) - Niaz, Basit; Iftikhar, Fatima; Kindermann, Markus K.; Jones, Peter G.; Heinicke, Joachim
Abstract: The acid‐catalyzed reactions of 5‐methyl‐2‐phosphanylaniline (1 ) with dialdehydes were studied. Whereas the reaction with glyoxal provides a mixture of two 1 H ‐1, 3‐benzazaphospholes, 2 and3, by concomitant reduction of a CHO group and C–C bond cleavage, respectively, the reaction with o ‐phthalic dicarbaldehyde provided in excellent yield the tetracyclic planar benzazaphosphole4, which was characterized by crystal structure analysis. The active hydrogen atoms, delivered by aromatization of a dihydrobenzazaphosphole intermediate, forms an N–CH2 bridge by reductive N ‐alkylation. Pyridine‐2, 6‐dicarbaldehyde reacts analogously but not chemoselectively and, thus, gives two isomers5 and6 . Condensation with pyridine‐2, 6‐dicarbaldehyde afforded the bis(benzazaphosphole)pyridine pincer ligand7, but along with 2‐(benzazaphospholyl)‐6‐tolylpyridine (8 ) by partial P–C bond cleavage. The high upfield 31 P NMR chemical shift of4 compared to those of normal benzazaphospholes indicates it to be a particularly π‐rich σ 2 P ligand. Abstract : Aromatization‐driven acid‐catalyzed condensations of the N, P‐diprimary compound1 with dialdehydes are coupled with hydrogen transfer reactions. With glyoxal and pyridine‐2, 6‐dicarbaldehyde this gives rise to side products, but with o ‐C6 H4 (CHO)2, high yields of4 are obtained. π‐Delocalization through the coplanar aryl rings causes high π‐density at the phosphorus atom.